2017
DOI: 10.1080/10942912.2017.1285788
|View full text |Cite
|
Sign up to set email alerts
|

Maillard volatiles in baked products as affected by feruloylated oligosaccharides from maize bran

Abstract: Feruloylated oligosaccharides (FOs) have been approved by the US Food and Drug Administration to be incorporated in baked goods. This research aimed to investigate the influence of FOs on flavour formation. Results revealed that the furfural content increased 5.2-, 6.7-, 5.6-, and 6.5-fold after 10 mg/g FOs was added and by 6.7-, 37.8-, 12.4-, and 64.5-fold after 50 mg/g FOs was added to aspartic acid/glucose, asparagine/glucose, glutamic acid/glucose, and dough models, respectively. Addition of FOs prevented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…On the contrary, significant positive correlations were found among phenolic compounds and furan derivatives from browning reactions (Maillard and caramelization reactions, Supplementary Figure S4), namely, furfural, furfuryl alcohol, 2-acetylfuran and 5-methylfurfural. These findings are in accordance with previous studies, which have demonstrated an increase in furfural and 5-methylfurfural by feruloylated oligosaccharides [29], possibly due to their pro-oxidant effect at high concentrations, therefore increasing browning reactions [78]. The positive correlations of some aldehydes with phenolic compounds can also be explained by the increase in these reactions, since aldehydes can also be originated during baking [11].…”
Section: Contribution Of Phenolic Compounds For Broas' Volatile Compositionsupporting
confidence: 92%
See 3 more Smart Citations
“…On the contrary, significant positive correlations were found among phenolic compounds and furan derivatives from browning reactions (Maillard and caramelization reactions, Supplementary Figure S4), namely, furfural, furfuryl alcohol, 2-acetylfuran and 5-methylfurfural. These findings are in accordance with previous studies, which have demonstrated an increase in furfural and 5-methylfurfural by feruloylated oligosaccharides [29], possibly due to their pro-oxidant effect at high concentrations, therefore increasing browning reactions [78]. The positive correlations of some aldehydes with phenolic compounds can also be explained by the increase in these reactions, since aldehydes can also be originated during baking [11].…”
Section: Contribution Of Phenolic Compounds For Broas' Volatile Compositionsupporting
confidence: 92%
“…p-Vinylguaiacol was also detected in broas, but not in maize flours. It has been described as an important odorant in other breads and baked products, derived from ferulic acid decarboxylation [8,28,29]. On the contrary, some compounds were lost after processing, such as aldehydes, alcohols and ketones, which may have been volatilized during baking [16,20], or participated in further reactions during bread making [35].…”
Section: Characterization Of the Volatile Composition Of Broasmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, feruloylated oligosaccharides (FOs) isolated from natural sources, such as wheat bran and rice, are considered to have health-promoting factors, due to prebiotic activity and activation of dendritic cells, among others [ 7 ]. Therefore, they have received approval from the US FDA to be used as additives in food products [ 8 ]. Several similar compounds have been synthesized in adequate yields, and tested in regard to their antioxidative activity, prebiotic activity, intracellular ROS modification, and cytotoxicity, with the aim to develop novel cosmeceutical and pharmaceutical formulations [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%